2018
DOI: 10.1002/epi4.12098
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet for treatment of intractable epilepsy in adults: A meta‐analysis of observational studies

Abstract: SummaryThe ketogenic diet (KD) is an effective treatment for children with drug‐resistant epilepsy and has been widely used in young children. Adult patients with intractable epilepsy would also benefit from this dietary treatment. However, only a few studies have been published, and the use of the KD in intractable epilepsy in adults has been limited. This meta‐analysis summarized the findings of the relevant published studies to identify the efficacy of the KD for the treatment of intractable epilepsy in adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 40 publications
(39 reference statements)
3
101
0
3
Order By: Relevance
“…16 Thus, in our small blinded study, the efficacy of the MCT treatment regarding >50% of seizure reduction (45%) is within the CIs of the ketogenic and Atkins diets' effects. The meta-analysis critically evaluated 16 prospective open-label studies with a total of 338 patients showing 62% completion on average in all studies, whereas 56% of 76 patients completed the 5 pure ketogenic diet studies.…”
Section: Comparison To Ketogenic Dietmentioning
confidence: 58%
See 4 more Smart Citations
“…16 Thus, in our small blinded study, the efficacy of the MCT treatment regarding >50% of seizure reduction (45%) is within the CIs of the ketogenic and Atkins diets' effects. The meta-analysis critically evaluated 16 prospective open-label studies with a total of 338 patients showing 62% completion on average in all studies, whereas 56% of 76 patients completed the 5 pure ketogenic diet studies.…”
Section: Comparison To Ketogenic Dietmentioning
confidence: 58%
“…Several studies with ketogenic diet or modified Atkin's diets have found similar antiseizure effects in children 14,15 and often adults 16 (although not consistently 17 ). The seizure frequency reductions in 5 of 11 participants treated with MCTs was encouraging, and, if confirmed, is comparable to other types of diets.…”
Section: Limitations Generalizability Interpretation Of Anti-seizmentioning
confidence: 96%
See 3 more Smart Citations